Jean Marie Despiau: Unjustly Maligned Physician in the Medical Service of the Nguyen - Thompson, C. Michele (Vietnam and the West, 2010)
Keywords: dept.his

Waging Wars of Quiet Survival: History of the Native Peoples of Connecticut. - Amerman, Stephen Kent (2010)
Keywords: dept.his; faculty_collection; sabbatical_report

War, Medicine and American Women in the Near East. - Metaxas, Virginia (2010)
Keywords: dept.his; faculty_collection; sabbatical_report

Urban Indians in Phoenix schools, 1940-2000 - Amerman, Stephen Kent (Indigenous education, 2010)
"In the latter half of the twentieth century, tens of thousands of Native American families moved to cities across the United States, some via the government relocation program and some on their own. In the cities, they encountered new forms of work, entertainment, housing, and education. In this study, Stephen Kent Amerman focuses on the educational experiences of Native students in urban schools in Phoenix, Arizona, a city with one of the largest urban Indian communities in the nation. The educational experiences of Native students in Phoenix varied over time and even in different parts of the city, but interactions with other ethnic groups and the experience of being a minority for the first time presented distinctive challenges and opportunities for Native students., Using oral histories as well as written records, Amerman examines how the Phoenix schools tried to educate and assimilate the Native students alongside Hispanic, Asian, black, and white students and how Native children, their parents, and the Indian community at large responded to this new urban education and the question of their cultural identity. Reconciling these pressures was a struggle, but many found resourceful responses, charting paths that enabled them to acquire an urban education while still remaining Indian."--Pub. desc.
Keywords: 20th century; 20th century; Education; 20th century; Indians of North America; 20th century; Public schools; 20th century; Urban schools; 20th century; Urbanization; Arizona; Cultural assimilation; Education; History; Indians of North America; Phoenix; Social aspects; award_winner; dept.his; faculty_collection

The Great Industrial War Framing Class Conflict in the Media, 1865-1950 - Rondinone, Troy (Rutgers University Press, 2010)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers. Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported.
Keywords: History; History; Social conflict; Labor disputes; United States; dept.his; faculty_collection

Bridges: Technology and the Social - Paddock, Troy R. E. (Environment, Space, Place, 2010)
Keywords: dept.his

Creating the Russian Peril: Education, the Public Sphere, and National Identity in Imperial Germany, 1890-1914 - Paddock, Troy R. E. (Camden House, 2010)
German attitudes toward and stereotypes of Russia before the First World War and how they were inculcated in the public.
Keywords: 1871-1918; 19th century; Education; 19th century; Nationalism; 20th century; Germany; 20th century; Nationalism; Foreign public opinion, German; Russia; Germany; Germany; Germany; Germany; Russia; History; History; Education; Political aspects; Press coverage; Public opinion; Relations; Russia; Russia; SCSU Faculty Scholar Award; award_winner; dept.his; faculty_collection

Trust and Violence in Atlantic History: The Economic Worlds of Venture Smith - Forbes, Robert P.; Richardson, David; Chandler, B. Saint (Venture Smith and the Business of Slavery and Freedom, 2010)
Keywords: dept.his

The political economy of mexico's independence heroes: selling public history in san miguel de allende - Covert, Lisa Pinley (The Latin Americanist, 2010)
Keywords: dept.his; peer-reviewed

The german myth of the east: 1800 to the present - Paddock, Troy R. E. (German Studies Review, 2010)
Keywords: dept.his; ⛔ No DOI found

The persistence of republicanism: class war talk, american style - Cassano, Graham; Rondinone, Troy (Labor Studies Journal, 2010)
The authors argue that there have been moments in American history when a class analysis entered into popular discourse. What has been "exceptional" about American history is the manner in which that class analysis emerged. When Americans speak the language of "class" and "class warfare," it is often clothed in the rhetoric of labor republicanism. That is, rather than offering a systemic analysis of capitalist processes, American labor republicanism offers a class analysis that sets a small set of bad acting "elites" and their dependents against the mass of American workers. The authors trace this discourse from Franklin Roosevelt's 1936 description of "economic royalists" to Lou Dobbs's nativist attack on "corporate elites" and undocumented workers. As the United States enters a new period of "class awareness" and economic crisis, this republicanism returns to haunt public discourse. © 2010 UALE.
Keywords: Franklin D. Roosevelt; Lou Dobbs; Marxian analysis; class warfare; dept.his; labor republicanism

Sinification as Limitation: Minh Mạng’s Prohibition on Use of Nôm and the Resulting Marginalization of Nôm Medical Texts - Thompson, C. Michele (Looking at it from Asia: the Processes that Shaped the Sources of History of Science, 2010)
For Vietnamese scholars in the late eighteenth and early nineteenth centuries reading and writing ability in both Chinese and Nôm (an ideographic writing system used to write Vietnamese) was considered an essential tool of scholarship and literary expression.
Keywords: Chinese Character; Imperial Examination System; Medical Text; Royal Court; Vietnamese Language; dept.his